Encyclopedia of forensic sciences - Houck, Max M. (Elsevier, 2022)
Encyclopedia of Forensic Sciences, Four Volume Set, Third Edition presents content that is logically built around the following sections and topics, via a taxonomic approach, as opposed to the previous old-style alphabetical mode, thus resulting in far easier navigation for the user. Sections first cover Biological issues, including Anthropology, DNA, Entomology, Genetics, Pathology, Serology, Fingerprints, Biometrics, and more. Next, a Chemical section covers Drugs, Explosives, Fire debris, Materials analysis, Polymers, General chemistry, Microscopy, Instrumental methods, Inks, Development methods (visualization of latent evidence), and more. Thirdly, a section on Physical covers Toolmarks, Firearms, Impression evidence, Documents and handwriting, fracture comparisons, etc. Additional sections cover Digital, including discussion on devices, storage, locations, servers, networks, consumer end-products, and black boxes (vehicles, planes, etc.). A final section covers Professional, with sections on philosophy, ethics, associations, accreditation, certification, licensing, legal issues and admissibility. All chapters in this update have been revised with the latest information in the field.